Safety and efficacy of single-incision sling for female stress urinary incontinence: 3 years' results. Issue 11 (November 2016) - Yildiz, Güner; Ceylan, Yasin; Ucer, Oktay; Arslan, Deniz; Çelik, Orçun; Gunlusoy, Bülent
Abstract Introduction and hypothesis The purpose of this study was to investigate the success and complication rates of single-incision sling for treating stress urinary incontinence (SUI), with a 3-year follow-up. Methods This study comprised 173 female patients with SUI or mixed urinary incontinence (MUI) with dominant SUI who underwent minisling procedure. All patients had positive cough stress test preoperatively; they were followed up for 3 years after surgery (1, 3, 6, 12 months, and yearly). Results Total follow-up was 36 months, and mean age 51 years (44–77); 128 (74 %) patients presented SUI and 45 (26 %) MUI. Objective and subjective cure and failure rates were 83.8 % (145 cases), 6.4 % (11 cases), and 9.8 % (17 cases), respectively. There were no differences in cure rates between 1 and 3 years. Mean body mass index was 28.7 (26.1–35.2), and mean operating time 7.9 min. (6.5–11.9). There were no major intraoperative complications. Eleven patients (6.4 %) had de novo urge incontinence that resolved using anticholinergic drugs; no patient had urinary retention. Vaginal mesh extrusion was reported in nine (5.2 %) patients. Conclusions The minisling system attained high success rates at 3 years' follow-up. The procedure was easy to learn and has lower complication rate.